Trade dispute over palm oil involving Indonesia, Malaysia, and the EuropeanUnion - Fajrul Akbar, Chalid; Fadri, Al; YULIAZA SYAWITRI, KARINA; KIRANA PUTRI, JINTA (JLAST : Journal of Law and Social Transformation, 2023)
Palm oil is a predominantly utilized raw ingredient in the production of food, cosmetics, andhousehold cleaning products. The global usage of this product is on the rise, rendering it asignificant asset in international commerce. Given its status as the leading palm oilproducer, Indonesia encounters trade obstacles from nations that impose restrictions onpalm oil imports based on environmental concerns, including deforestation and greenhousegas emissions. The European Union, a significant recipient of Indonesian palm oil exports,has implemented the Renewable Energy Directive (RED) and RED II. These regulationsimpose limitations on the use of palm oil in biodiesel starting from 2021 and progressivelyprohibit it entirely by 2030. These rules, although designed to safeguard the environment,are seen by some as protectionist measures aimed at safeguarding local biofuel producers.The governments of Indonesia and Malaysia have voiced concerns and are actively pursuingequitable and enduring resolutions to preserve their market entry